Efeito da ocupação urbana e do uso de técnicas compensatórias sobre o escoamento superficial direto da bacia hidrográfica do córrego Santa Maria do Leme - São Carlos - SP - Teixeira, Weverton de Souza (Universidade Federal de São Carlos, 2024)
The process of urbanization and growth of cities generates interference in the flow of water in urban areas. Given this situation, new drainage techniques have been used with the aim of mitigating or at least minimizing the hydrological effects of urban occupation. Advances in research demonstrate that the use of compensatory techniques, such as water basins, detention, serves the hydrological function of dampening the flows generated in the basin, reducing the risk of flooding and flooding downstream. In this way, this work aims to main objective to compare the hydrographs generated in pre and post occupation scenarios of Santa Maria do Leme basin - São Carlos, to obtain quantitative data from the flows and verification of how human occupation and compensatory techniques affect them. To this end, the area was characterized in all aspects relevant to the flow, type of soil, type of coverage, vegetation, among others, and subsequent allocation of parameters for defining the flow for the different compositions. From the data surveyed, it was possible to generate the hydrographs for the defined project rainfall, obtaining, for the different scenarios, the characterization of flows in the basin. The results obtained show that the basin in its natural state has a peak flow 17.22 times lower and concentration 1.68 times higher, when compared to its current state of occupation. Also it is concluded that the detention basins amortized the peak flow by 16.20%, showing an alternative to reduce the effects of urban occupation on runoff.
Effect of urban occupation and the use of compensatory techniques on runoff from the Santa Maria do Leme basin - São Carlos - SP
Keywords: Técnicas compensatórias; Ocupação urbana; Drenagem urbana; SWMM; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO